A method of reconstruction of clinical gas-analyzer signals corrupted by positive-pressure ventilation. - Farmery, A; Hahn, C (2001)
The use of sidestream infrared and paramagnetic clinical gas analyzers is widespread in anesthesiology and respiratory medicine. For most clinical applications, these instruments are entirely satisfactory. However, their ability to measure breath-by-breath volumetric gas fluxes, as required for measurement of airway dead space, oxygen uptake, and so on, is usually inferior to that of the mass spectrometer, and this is thought to be due, in part, to their slower response times. We describe how volumetric gas analysis with the Datex Ultima analyzer, although reasonably accurate for spontaneous ventilation, gives very inaccurate results in conditions of positive-pressure ventilation. We show that this problem is a property of the gas sampling system rather than the technique of gas analysis itself. We examine the source of this error and describe how cyclic changes in airway pressure result in variations in the flow rate of the gas within the sampling catheter. This results in the phenomenon of "time distortion," and the resultant gas concentration signal becomes a nonlinear time series. This corrupted signal cannot be aligned or integrated with the measured flow signal. We describe a method to correct for this effect. With the use of this method, measurements required for breath-by-breath gas-exchange models can be made easily and reliably in the clinical setting.